Fecal microbiota transplantation improves growth performance of chickens by increasing the intestinal Lactobacillus and glutamine - Yibin Xu; Kuan Chen; Yulin Huang; Yifeng Yan; Weiqin Zhang; Jinghong Tian; Dexiang Zhang; Manqing Liu; Qinghua Nie (Poultry Science)
Chicken meat is an essential source of high-quality animal protein, mainly derived from slow-growth chicken (SC) and fast-growth chicken (FC) breeds. Skeletal muscle is a highly adaptable tissue that is influenced by breed differences and the gut microbiome. Investigation whether remodeling the gut microbiota by fecal microbiota transplantation (FMT) improves chicken growth is an interesting question. We compared the gut microbial composition of eight breeds of SC (Xinghua chicken, Yangshan chicken, Zhongshan Salan chicken, Qingyuan Partridge chicken, Huiyang Bearded chicken and Huaixiang chicken) and FC (Xiaobai chicken and White rock chicken). Fecal microbiota from donor FC (Xiaobai chickens) with superior growth performance were transferred to SC (Xinghua chickens). The effects of FMT on growth performance, metabolic profile and gut microbiome of recipient chickens were evaluated. We found significant differences in gut microbial composition, with a higher abundance of Bacteroidetes in SC and a higher abundance of Firmicutes in FC. Xiaobai chickens with better growth performance and abundant Lactobacillus, and FMT significantly enhanced growth performance, the expression of mRNA (MYOG, MYF5, MYF6 and IGF1) related to breast and leg muscle development and improved the villus/crypt ratio in the jejunum. FMT altered the microbiota in the duodenum, jejunum, and ileum, increased Lactobacillus abundance, decreased the relative mRNA expression of the intestinal inflammatory factors (IL-1β, IL-6 and TNF-α), increased glutamine levels in the host, including in muscle tissues and intestinal contents, and Spearman correlation analysis indicated that the relative abundance of Lactobacillus was positively correlated with glutamine levels. Additionally, antibiotic treatment reduces glutamine levels in the intestines, blood, and muscle tissues of chickens. Glutamine can increase the expression of cyclinD1, cyclinD2, cyclinB2, MYOG, MYF5, MYF6 and IGF1 mRNA to promote chicken myoblasts proliferation and differentiation. This study found that the SC and FC gut microbes were significantly different, and the FC chicken gut microbes were able to reshape the FC gut microbiota through FMT, i.e., higher Lactobacillus, promoted chicken myoblasts proliferation and differentiation and growth performance by increasing glutamine levels.